Sistem Pemantauan Nutrisi Air Pada Tanaman Hidroponik Model Rakit Apung - Fadhil Albar; Irving Vitra Paputungan; Kurniawan Dwi Irianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Hydroponics is an alternative method of planting that replaces soil media with water. This planting model can optimize land use which is currently getting less and less because hydroponics does not require a large planting space. Hydroponics has one of the planting techniques, namely the floating raft hydroponic model. Floating raft hydroponic has a planting style with a flat plane so that water can pool under the plant. This model is not only cheap, but also easy to make for ordinary people. However, this model has a drawback, namely the owner must always pay extra attention to the plants because floating raft hydroponic uses stagnant water without circulating water or air, this can make the nutrient content in the water poison the plants themselves. In addition, water levels can cause fungus on the roots of these hydroponic plants. A system was created to monitor nutrient solution levels, water acidity levels, temperature values, humidity and light intensity. These parameters are monitored using several sensors, namely: Total Dissolved Solid (TDS) sensor, water pH sensor, water level sensor, light intensity sensor and temperature and humidity sensor controlled by a microcontroller with the ESP32 model. The results of the sensor recording are displayed on the blynk platform which can provide real time plant status. With this system the owner can monitor in real time and can increase awareness when caring for hydroponic plants with the floating raft hydroponic model.